(untitled) (Revista Internacional de Formação de Professores, 2023)
Modernity promises equality and highlights the role of education and the school in the formation of citizens, but its implementation as a result of a school for all is called into question. This article problematizes the power of the school to create the new humans for another society, points out the potentials and limits of its organizational rationality in democratic Portugal, distinguishes several faces of hope in the mediation of education for the transformation of society and, advocating a fairer school, it identifies tensions and challenges of the current curricular and pedagogical policy.